Climate Minsky Moments and endogenous financial crises - Matthias Kaldorf; Matthias Rottner (Deutsche Bundesbank, 2024)
Does a shift to ambitious climate policy increase financial fragility? In this paper, we develop a quantitative macroeconomic model with carbon taxes and endogenous financial crises to study such "Climate Minsky Moments". By reducing asset returns, an accelerated transition to net zero exerts deleveraging pressure on the financial sector, initially elevating the financial crisis probability substantially. However, carbon taxes improve long-run financial stability since permanently lower asset returns reduce the buildup of excessive leverage. Quantitatively, we find that the net financial stability effect of ambitious climate policy is positive for low but empirically plausible social discount rates.
Keywords: E32; E44; G20; Q52; Q58; 330; Climate Policy; Financial Stability; Financial Crises; Transition Risk